MOTOR SKILLS TRAINING ASSISTANCE FOR CHILDREN WITH SPECIAL NEEDS THROUGH HIGH-INTENSITY INTERVAL TRAINING: PENDAMPINGAN PELATIHAN KEMAMPUAN MOTORIK ANAK BERKEBUTUHAN KHUSUS MELALUI LATIHAN HIGH INTENSITY INTERVAL TRAINING - Gatot Jariono; Nurhidayat Nurhidayat; Eko Sudarmanto; Ardhian Tomy Kurniawan; Chandra Triadi; Maimunah Nur Anisa (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
This community service activity was based on discussions and observations with teaching staff for children with special needs at SLBN Karanganyar and Sukoharjo, Central Java Province, about difficulties assisting and teaching children with special needs. Based on the results of observations and discussions with teaching staff, the researcher and a servant provide solutions in the form of assisting the motor skills of children with special needs through high-intensity interval training. Motor ability is an essential indicator of fitness for each individual, closely related to the quality of life. At the same time, high-intensity interval training is an alternative in the form of a solution to improve movement abilities, especially for children with special needs. This community service aims to provide understanding and development of science and technology to teaching staff for children with special needs to improve motor skills through high-intensity interval training. The methods used in community service are documentation, interviews, and observations. The results of this study indicate that one way to improve motor skills is through high-intensity interval training